2021
DOI: 10.1186/s12916-021-01910-z
|View full text |Cite
|
Sign up to set email alerts
|

When a pandemic and an epidemic collide: COVID-19, gut microbiota, and the double burden of malnutrition

Abstract: Background It is estimated that the COVID-19 pandemic will drastically increase all forms of malnutrition. Of particular concern, yet understated, is the potential to increase the double burden of malnutrition (DBM) epidemic. This coexistence of undernutrition together with overweight and obesity, or diet-related non-communicable disease (NCD), within low- to middle-income countries (LMICs) is increasing rapidly. Although multiple factors contribute to the DBM, food insecurity (FI) and gut micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…The DBM is defined by WHO as "the coexistence of undernutrition along with overweight, obesity or diet-related non-communicable diseases (NCD), within individuals, households and populations, and across the life-course" and may be aggravated by poor environmental circumstances and genetic predispositions (1). Although a large proportion of deaths among children under five are attributed to malnutrition, overweight and obesity in this age group and older are on the rise (5). The increased risk of NCD related with the nutritional transition in developing countries is a public health concern, due to the potential economic impact and oversaturation of the health system infrastructure (6).…”
Section: Dietary Changes In Developing Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…The DBM is defined by WHO as "the coexistence of undernutrition along with overweight, obesity or diet-related non-communicable diseases (NCD), within individuals, households and populations, and across the life-course" and may be aggravated by poor environmental circumstances and genetic predispositions (1). Although a large proportion of deaths among children under five are attributed to malnutrition, overweight and obesity in this age group and older are on the rise (5). The increased risk of NCD related with the nutritional transition in developing countries is a public health concern, due to the potential economic impact and oversaturation of the health system infrastructure (6).…”
Section: Dietary Changes In Developing Countriesmentioning
confidence: 99%
“…The dynamic gut microbial ecosystem is directly influenced by the diet and by its bidirectional interaction with the health of the host. In the context of DBM, literature points out that changes in the microbiota can be profoundly influenced by both undernutrition and obesity (5). Long-lasting effects of undernutrition in early life can be attributed to interconnected biological pathways, involving imbalance of the gut microbiome, inflammation, metabolic dysregulation, and impaired insulin signaling (8).…”
Section: Dietary Imbalance and Inflammation: From The Gut To The Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…This disease increases the difficulties and life burdens on the humanity beside the global malnutrition and hidden hunger. It is reported that all forms of malnutrition not might only increase drastically due to the COVID-19 pandemic but the potential of the double burden of malnutrition epidemic, of particular concern, will be also increased ( Littlejohn and Finlay, 2021 ). Therefore, some studies recently published about the production of biofortified crops enriched in some nutrients like Zn, which has the ability to improve the respiratory disorders and pneumonia beside the susceptibility to the outbreak of COVID-19 ( El-Ramady et al, 2021a , Gastélum-Estrada et al, 2021 , Okwuonu et al, 2021 ).…”
Section: Challenges Of Biofortification In the Era Of Covid-19mentioning
confidence: 99%
“…In 2020, planet Earth faced a huge threats or challenges, including extreme snow disasters, floods and droughts, in Europe, North America, and Asia, unprecedented locust-attacks in Africa, and the global COVID-19 pandemic (Jiang et al 2021). These challenges have had devastating impacts on food security, human health, and the environment (Littlejohn and Finlay, 2021). The human health needs essential nutrients and nutritional compounds and lack of them causes the malnutrition, which means "nutrient deficiency including shortages of vitamins and minerals" (Jiang et al 2021).…”
Section: Introductionmentioning
confidence: 99%